FORMATION OF LOW-TEMPERATURE MYLONITES AND PHYLLONITES BY ALKALI-METASOMATIC WEAKENING OF FELSIC VOLCANIC ROCKS DURING PROGRESSIVE, SUBDUCTION-RELATED DEFORMATION - van Staal C.R.; Rogers N.; Taylor B.E. (My University, 2001)
Dacitic to rhyolitic volcanic rocks of the Spruce Lake nappe experienced two phases of alkali-metasomatism as a result of fluids channelling along shear zones. The shear zones formed during a progressive, thrust-related deformation associated with underplating and incorporation of the volcanic rocks into the Brunswick subduction complex of northern New Brunswick. The fluids mainly represent chemically and isotopically modified seawater released by dewatering of the associated underthrusted shaly sedimentary rocks. Both phases of metasomatism weakened the felsic rocks, leading to strain localisation. Albitisation of felsic volcanic rocks as a result of Na-metasomatism during underthrusting facilitated formation of mylonites near peak high-pressure metamorphism (330-370°C, 600-800MPa). The mylonites are preferentially preserved in the roof-thrust shear zone of the Spruce Lake nappe. Core-mantle structures, bulging and crystallographically preferred orientations indicate that albite behaved more ductilely than K-feldspar. The ductility of albite at these low temperatures is interpreted as a function of abundant intragranular fluids. Phengite-rich phyllonites formed after peak high-pressure metamorphism during uplift by out-of-sequence thrusting. These phyllonites are generally characterised by a slight gain in K and loss of Na and are best developed in the basal shear zones of the Spruce Lake nappe.